Beneficial effects of polyherbal formulation (Bronco-T) on formaldehyde-induced lung toxicity in male Wistar rats - Sholapuri, Payani (Toxicol Res (Camb), 2020)
Polyherbal compound (Bronco-T) has been extensively used as a traditional medicine for various therapies. However, very few report studies on anti-inflammatory and lung regeneration properties are evidenced. In the present study, we evaluated the beneficial actions and anti-inflammatory properties of polyherbal medicine, Bronco-T, exhibited by treating the lungs of rats exposed to formaldehyde to evaluate the beneficial properties. For this study, we divided into five groups’: i.e. Group-I served as a control and the other four groups such as II, III, IV, and V are experimental. All animals maintained by regular feed and water ad libitum during the study. Formaldehyde vapors exposure at a single period of time (1 hour) daily (40%formaldehyde at room temperature) for 21 days period exposed all groups. The Bronco-T extracts about 50 mg/kg BW administered to experimental groups and group IV rats treated with 500μ grams/Kg BW salbutamol. To understand the impact of formaldehyde exposure on the beneficial effects of Bronco-T, we evaluated hematological parameters, bronchoalveolar lavage (BAL), histamine levels, and histological alterations of lung architecture. Formaldehyde-induced adverse effects in lung and increased histamine levels in BAL compared to Bronco-T-treated rats act as a preventive immunological role in blood toxicity and recovery of lung architecture in Bronco-T-treated rats. This study showed the evaluation of antihistamine levels through HPLC analysis. Bronco-T has antioxidant and anti-histamine properties as the widest therapeutic window, and we continue to evaluate the pharmacological evaluations needed in our further studies.